Network Security Strategy with VLANs and Access Control Lists: Case Studies and Implementation - Djuanda, Dhafa Nugraha (SAN Scientific, 2024)
This research focuses on the design and implementation of network security strategies using Virtual Local Area Network (VLAN) and Access Control List (ACL) at PT Pegadaian Kalibata Branch. The background of this research is the increasingly urgent need for a network security system that is able to protect infrastructure from various complex cyber threats, especially for financial business entities. In an effort to improve network security, Virtual Local Area Networks (VLANs) are used to separate network traffic based on business needs, while Access Control Lists (ACLs) are implemented to set security rules in controlling network traffic. This study uses observation, interview, and literature study methods to collect relevant data. The results show that the implementation of Virtual Local Area Network (VLAN) and Access Control List (ACL) can effectively improve network security, reduce the risk of cyberattacks, and improve bandwidth efficiency. However, some challenges such as missing configurations and bandwidth limitations still have to be overcome to achieve optimal results. This research is expected to contribute to the development of a better network security system for PT Pegadaian and other financial organizations.